Investigating cytokine responses to different strains of Mycobacterium tuberculosis - Booi, Zandile (Department of Clinical Laboratory Sciences, 2022)
Mycobacterium tuberculosis (Mtb), the causative agent of human tuberculosis (TB), is one of the world's most prevalent fatal pathogens, infecting one third of the global population. The highly specialised pathogen that infects humans today evolved from a group of bacteria, known as the Mycobacterium tuberculosis complex (MTBC). It is divided into different lineages, based on phylogeography and genetic structure. It is well established that infection with different strains can lead to different types of innate immune responses. Recent studies indicate differences in the adaptive immune response (IL-22 and IL-17) induced by various Mtb strains, however these differences have not been clearly defined. The aim of this study was to investigate CD4+ T cell adaptive cytokine responses (IFN-γ, IL-22 and IL-17) in blood from human volunteers with prior exposure to Mtb, when stimulated with different strains within the MTBC, using a whole blood assay, flow cytometry and enzyme-linked immunosorbent assay (ELISA). My results indicate that the frequency of IFN-γ and IL-22-producing CD4+ T cells was similar for the two strains, as no significant differences were observed. In contrast, IL-17 responses for HN878 was almost 2-fold higher than H37Rv (p=0.04), consistent with published observations. Moreover, three additional Mtb strains (Indo-oceanic, East African-Indian and the Euro-American outbreak strain CDC1551) were tested for their ability to detect cytokine responses. While all five strains enabled the detection of Mtb-specific CD4+ T cell IFN-γ, IL22 and IL-17, no significant differences were observed when comparing the responses between strains. The highest responses were observed for IFN-γ, followed byIL-22 and IL17. In addition to flow cytometry, soluble cytokine concentrations of IFN-γ and IL-22 were examined in plasma in whole blood stimulated with Mtb lysate derived from H37Rv and HN878, using an ELISA. Responses were tested at both 24 and 48 hours of stimulation, and while median responses were higher at the later time point, they were not significantly different. IFN-γ showed no difference between H37Rv and HN878 at 24 hours in the ELISA. In contrast, HN878 IFN-γ responses were lower than H37Rv at 48 hours (p=0.04). The amount of secreted IL-22 did not differ significantly between the twos trains at either time point. Further work is required to confirm these findings in a larger cohort to understand differences in adaptive responses to different Mtb strains. In conclusion, understanding Mtb strain modulation of host immune function is of major importance, as it may provide better insights into human TB immunity and could assist in the development of an effective TB vaccine.